A Comparative Study of the Landfall Precipitation by Tropical Cyclones ARB 01 (2002) and Luban (2018) near the Arabian Peninsula - Yusheng Cui; Haibin Lü; Dawei Shi; Chuqi Xia; Changming Dong (Remote Sensing, 2022)
Considering the high risk of flooding during tropical cyclones (TCs), there is great practical significance in researching and predicting precipitation during TC landfalls. Using NECP FNL reanalysis data and GPM_MERGIR datasets, two TCs with similar trajectories, ARB 01 in 2002 and Luban in 2018, were analyzed. For ARB 01 and Luban, there are separate effects of wind shear at different heights on the development of vertical motion. Meridional wind shear affects the main deviation direction of vertical motion (downshear), while zonal wind shear mainly affects the deviation direction of vertical motion to the left or right of downshear. The divergent configuration of wind promotes the development of vertical motion. The influence of wind speed provided ideal conditions for ARB 01 to generate symmetric precipitation along its path when it made landfall. Additionally, more water vapor support was obtained from the southern Indian Ocean, which enabled ARB 01 to have a larger and broader average precipitation rate after landing.